Patients' Intentions to Use a Physician-Provided Digital Health Information Service - Paula Memenga; Elena Link (University of Zurich, IKMZ - Department of Communication and Media Research, 2024)
Patients require adequate, high-quality health information, but their most trusted source, physicians, have scarce time resources. A physician-provided digital health information service (DHIS) offers new solutions to this challenge. Guided by the extended unified theory of acceptance and use of technology (UTAUT2), this study examined patients' intentions to use such a service. The model was supplemented by informational social norms and eHealth literacy. An online survey with a stratified German sample (N = 1,000) was conducted. In a fictitious scenario, the DHIS was described as a web-based platform for tailored health information. Data were analysed using a multiple linear regression analysis and a mediation analysis. The regression model explained 57.8% of the variance of usage intentions. The factors performance expectancy, effort expectancy, hedonic motivation, time value, and habit were positively associated, and facilitating conditions were not associated with usage intentions. eHealth literacy showed a weak but significant association with usage intentions, but social norms were not linked to it. The effect of eHealth literacy was mediated by effort expectancy and habit. Our results support the need for digital methods of information provision. Communication about DHIS should particularly address its personal value for patients' knowledge, decision-making, and health status.